Philosophical Framing in the Classroom: How Science Teachers Deconstruct the Nuclear Energy Debate - Dindin Nasrudin; Chaerul Rochman; Wahyuni Handayani; Irawan; Sani Insan Muhammadi (Jurnal Pendidikan Sains Indonesia, 2026)
This qualitative phenomenological study investigates how physics teachers philosophically frame the nuclear energy debate in their pedagogical practice. Conducted with five Indonesian physics teachers pursuing graduate studies in science education, the research employed in-depth interviews and document analysis to explore how teachers utilize philosophical frameworks to navigate this complex socio-scientific issue. The findings reveal that teachers systematically employ core concepts from the philosophy of science—including Popperian demarcation, Kuhnian paradigms, and theory-ladenness of observation—to deconstruct the nuclear energy controversy. Their philosophical understanding enables them to transcend technical risk-benefit analyses and instead frame nuclear energy as a dynamic, value-laden, and socially-embedded domain of knowledge. Furthermore, the study demonstrates how teachers translate these philosophical frameworks into innovative pedagogical strategies, particularly through Problem-Based Learning (PBL), Inquiry Learning, and structured evidence-based debates that engage students in authentic scientific inquiry and critical reflection. This research underscores the vital role of philosophy of science in empowering educators to transform controversial topics into meaningful learning experiences that develop students' critical thinking skills and scientific literacy. The study contributes to science teacher education by highlighting how philosophical literacy enhances teachers' capacity to foster democratic discourse around complex technological issues in the classroom.